Holistic Approach in Internalizing Multicultural Values in Elementary Schools through Islamic Education Learning - Mauhibur Rokhman; Nur Kalim; Muhammad Anas Ma`arif (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
This research examines the process of internalising multicultural values in Islamic Religious Education (PAI) learning at Saraswati Elementary School in Tabanan, Bali. Using a qualitative approach with observation, interview, and documentation methods, this study aims to analyse the implementation and impact of multicultural education in an elementary school that has students with diverse backgrounds. The results show that SD Saraswati Tabanan has successfully implemented a holistic approach in internalising multicultural values, not only through formal learning in the classroom, but also through various extracurricular activities and school programs. Various learning methods, including traditional and contemporary approaches, have proven effective in instilling multicultural values. School activities such as orphan benefits and fundraising for victims of natural disasters provide a practical platform for students to apply the values of tolerance, empathy and co-operation. The results can be seen in changes in students' attitudes and behaviour, which show a high level of tolerance and mutual understanding in daily interactions. Although there are still challenges, especially in providing facilities for non-Muslim students, the experience of SD Saraswati Tabanan can be a valuable model for other schools in Indonesia in developing effective multicultural education.